Pengaruh Modal, Tingkat Upah, Penyerapan Tenaga Kerja Terhadap Produksi Kerajinan Patung Batu Padas Kecamatan Sukawati - adie perdana, gede herry; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
Craft industry has a very important role in Bali in general and in Gianyar regency especially in providing employment opportunities for the community. The development of craft industries will be able to lower the unemployment rate for employment and reduce poverty. The purpose of this study to determine the relationship directly or indirectly capital, the level of wage increases on employment and industrial production craft sculpture rocks in District Sukawati Gianyar regency. Data collection methods used in this study include observation, interviews and in-depth interviews. Data analysis technique used is the analysis track / path analysis and Sobel test to analyze the indirect influence through an intervening variable. The results were obtained conclusion that capital and wage levels have direct and significant effect on employment limestone sculpture crafts industry. Variable capital, wages and employment and significant direct effect on the production of handicraft industry limestone sculpture in District Sukawati Gianyar regency. Variable employment is a mediating variable between variable capital and the level of wages on production
Keywords: Keywords:Capital, Wage Rate, Absorption Labor, Production